Extended pointers for memory protection in single address space systems. (March 2020) - Lopriore, Lanfranco; Santone, Antonella
Abstract: With reference to a single address space paradigm of memory addressing, we identify a set of mechanisms aimed at preserving the integrity of the virtual space of a given process from erroneous or fraudulent access attempts originated from other processes. These mechanisms guarantee a level of protection that is, in many respects, superior to that of a traditional multiple address space environment. We introduce extended pointers as a generalization of the concept of a memory address, which includes a password and an access authorization. A universally known, parametric one-way function is used to assign passwords. A specialized address translation circuitry supports memory reference and protection at the hardware level. A small set of protection primitives forms the process interface of the protection system. An indication of the flexibility of the proposed protection paradigm is given by applying extended pointers to the solution of a variety of protection problems.